(untitled) (Plant Tissue Culture and Biotechnology, 2026)
An efficient in vitro regeneration protocol was developed using bulb explants of Easter Lily (Lilium longiflorum Thunb.). MS medium supplemented with 1.5 mg/l BAP and 0.5 mg/l NAA induced callus formation within 20-30 days imcluding 93.33% of success rate. The regenerative calli were then transferred to a shoot initiation medium containing 2.5 mg/l BAP and 0.5 mg/l NAA, leading to 95.56% of the calli initiating shoots within 20-25 days. The initiated shoots were subsequently transferred to a medium containing 3.0 mg/l BAP, which proved effective for shoot multiplication and proliferation, producing a mean number of shoots 35.0 ± 1.0 per explant. Healthy shoots were then placed in a root induction medium containing full-strength or half-strength MS medium supplemented with IAA at a concentration of 0.5 mg/l or 1.0 mg/l. This treatment induced efficient rooting, with an average root length of 7.2 ± 2.0 cm and a mean of 9.0 ± 1.0 roots per plantlet on full-strength MS medium supplemented with 0.5 mg/l IAA.. The well-rooted plantlets were transplanted into pots containing different ratios of garden soil, cocopeat, and vermicompost. The acclimatized plantlets were successfully established under field conditions. Thus, the developed in vitro regeneration protocol serves as a robust and scalable method for producing high-quality L. longiflorum plantlets, expected to provide substantial benefits for both research and commercial floriculture industries in Bangladesh. Plant Tissue Cult. & Biotech. 35(2): 417-426, 2025 (December)